PENGARUH GAYA KEPEMIMPINAN SITUASIONAL TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. INDONESIA GLOBAL DI MAKASSAR - Sudirman, Sudirman; Badrussaman, A. Badrussaman (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
This study aims to review and analyze the influence of managers' situational leadership style on employee work motivation as well as to find out which manager leadership style is most influential on increasing employee work motivation at PT. Global Indonesia in Makassar, the research method is survey. The research population is employees at PT. Indonesia Global In Makassar as many as 111, then 90 samples were taken with simple-random sampling techniques, data collection techniques through questionnaires, interviews, and documentation as support. Data analysis techniques are multiple linear regressions to determine the influence of free variables on partially and simultaneously bound variables. The results of research show that the manager's situational leadership style has a significant effect both simultaneously and partially in increasing employee work motivation at PT. Global Indonesia in Makassar with a positive direction, while the participatory leadership style is the most dominant influential leadership style.